Comparative study on Dynamic Voltage Restorer (DVR) and Distribution Static Compensator (DSTATCOM) techniques for voltage sag mitigation - Norshafinash, Saudin; Latifah, Mohamed; M. A., Mohamed; N. M., Nayan; Nor Shahida, Jamoshid (Universiti Malaysia Perlis (UniMAP), 2011)
Organized by School of Electrical System Engineering, Universiti Malaysia Perlis (UniMAP), 7th - 8th December 2009 at Parkroyal Hotel, Penang, Malaysia.